Handling Language Difficulties in Mathematical Word Problems Using Innovative Language-Supportive Pedagogy - Emily Christopher; Francis William (Journal of Research in Mathematics, Science, and Technology Education, 2026)
This study examined the extent of language-related difficulties encountered in teaching and learning secondary school mathematics word problems and subsequently developed exemplary Language-Supportive Pedagogical (LSP) materials to mitigate these difficulties. The idea was raised because, despite the importance of mathematics in human life, reports show that its achievement worldwide is still low. In Tanzania, for example, the subject has performed poorly in national examinations, particularly in ordinary-level secondary education. According to national examination reports based on item analysis, students attempt questions incorrectly because they do not understand the demands of the questions, likely due to low language proficiency. This study aimed to develop LSP materials that help teach mathematics through user-friendly language. The social constructivism theory of learning, building on the work of van den Akker (2010), was employed to provide guidelines and principles for material design. After being piloted to gauge their feasibility, the language supporting materials were ultimately assessed to determine their effectiveness. Tests, questionnaires, interviews, and observation were used to gather both qualitative and quantitative data in an adaptation of developmental research. The study involved three secondary schools (a pilot school with 40 students, an intervention school with 48 students, and a control school with 41 students), three mathematics experts from the university, four teachers of mathematics, and Form IV students purposely sampled. The proposed design guidelines and principles for the material employed LSP characteristics that focused on simple language and context-based activities, pictures, real materials, and a mathematics glossary. Findings from formative and semi-summative evaluations indicate that teachers and students showed the need for language supportive materials in mathematics that could address the observed difficulties. During the post-test, students who were taught using LSP materials performed better than those who used the conventional approach.